Sociodemographic Characteristics and Physical Activity in Patients with COPD: A 3-Month Cohort Study. (1st July 2021) - Dragnich, Alex G.; Yee, Nathan; Gylys-Colwell, Ina; Locke, Emily R.; Nguyen, Huong Q.; Moy, Marilyn L.; Magzamen, Sheryl; Fan, Vincent S.
Abstract: Decreased physical activity (PA) is associated with morbidity and mortality in COPD patients. In this secondary analysis of data from a 12-week longitudinal study, we describe factors associated with PA in COPD. Participants completed the Physical Activity Checklist (PAC) daily for a 7- to 8-day period. PA was measured monthly using the Physical Activity Scale for the Elderly (PASE). At three different time points, daily step count was measured for one week with an Omron HJ-720ITC pedometer. The 35 participants were primarily male (94%) and White (91%), with an average age of 66.5 years and FEV1 44.9% predicted. Common activities reported on the PAC were walking (93%), preparing a meal (89%), and traveling by vehicle (96%). PA measured by both PASE score ( p = 0.01) and average daily step count ( p = 0.04) decreased during follow-up. In repeated measures multivariable modeling, participants living with others had a higher daily step count (ß = 942 steps, p = 0.01) and better PASE scores (ß = 46.4, p < 0.001). Older age was associated with decreased step count (ß = −77 steps, p < 0.001) whereas White race was associated with lower PASE scores (ß = −55.4, p < 0.001) compared to non-White race. Other demographic factors, quality of life, and medications were not associated with PA. A better understanding of the role of social networks and social support may help develop interventions to improve PA in COPD.